Implementasi Perjanjian Tura Jaji di Paga Kabupaten Sikka - Antonia Alfiayu Zigha Nanga; Sonia Klara Seke; Ignecya Titania Katoda; Stefanus Don Rade (Universitas Sains dan Teknologi Komputer, 2024)
Exploring the relationship between contractual law and the local wisdom of